1977
DOI: 10.1111/j.1755-3768.1977.tb08277.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contents of Sodium, Potassium, Water and Dry Matter in Human Senile Cataractous Lenses in Relation to Anterior Capsular/Subcapsular Opacity

Abstract: In 49 human senile cataractous lenses the sodium and potassium concentrations of the lens water as well as the water and dry weight percentages were examined. It was found justifiable to classify the lenses into three categories on the basis of correlated biomicroscopic and biochemical findings: 1. Immature cataractous lenses without anterior capsular/subcapsular opacity (ac-sco) were characterized by low CNaL+, high CKL+ and low sums of CNaL++CKL+. 2. Immature cataractous lenses with ac-sco were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…Later it has been suggested that proteins of low molecular weight leak from the lens to the aqueous during senile cataractogenesis (Mach 1963;Charlton k van Heyningen 1968;van Heyningen 1972). In accordance with this, Klauber 8: Bruun Laursen (1977) found low dry weight (= protein) percentages in totally opaque lenses. Since such lenses are small as compared with e. g. the thicker immature cataractous lenses, totally opaque lenses obviously contain less protein than do thick immature cataractous lenses.…”
Section: Into the Aqueous?supporting
confidence: 72%
“…Later it has been suggested that proteins of low molecular weight leak from the lens to the aqueous during senile cataractogenesis (Mach 1963;Charlton k van Heyningen 1968;van Heyningen 1972). In accordance with this, Klauber 8: Bruun Laursen (1977) found low dry weight (= protein) percentages in totally opaque lenses. Since such lenses are small as compared with e. g. the thicker immature cataractous lenses, totally opaque lenses obviously contain less protein than do thick immature cataractous lenses.…”
Section: Into the Aqueous?supporting
confidence: 72%
“…5) The central anterior lens structures were chosen for Na-K ATPase activity assay because cation transport appears to be most active here (Becker & Cotlier 1962). The C,,+/C,+ ratio of ACSCO lenses increases with increasing extent of ACSCO (Klauber & Bruun Laursen 1977). As indicated by Duncan (1973) such a change may be due to 1) decreasing lenticular Na-K ATPase activity or 2) increasing permeability of the ion-restricting lens membranes.…”
Section: Na-k Atp'ase Activity In Senile Cataractsmentioning
confidence: 93%
“…In addition, the blank tubes contained 1 mM ouabain. The protein concentration was approximately 0.3-0.6% (calculated from disc weights and protein percentage -Klauber & Bruun Laursen 1977). Furthermore, in 25 lenses the activity of the Na-K ATP'ase in the anterior structures of each individual lens was determined at the following C,,+/C,+ ratios in the assay medium: 6/150,36/120,8l/75 meqil.…”
Section: Biochemical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations